2020
DOI: 10.18203/issn.2454-5929.ijohns20201280
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on benign paraoxysmal positional vertigo in a tertiary health care facility of North India

Abstract: <p class="abstract"><strong>Background:</strong> Benign paraoxysmal positional vertigo (BPPV) has been attributed to be one of the commonest causes of vertigo presenting to the clinician. However, this often remains undiagnosed and undertreated, epidemiology remaining an underexplored territory for this disorder.</p><p class="abstract"><strong>Methods:</strong> A study was carried out at outpatient clinic, Ear Nose Throat, Head and Neck services, Dayanand Medical Colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In the study by Munjal et al 84.81% of the patients got symptomatic relief with Epley maneuver. 2 Through a series of head movements, the crystals are returned to the utricle, where they are either absorbed or eliminated by the endolymphatic sac. 21 However a study done by Kavathia et al showed that the Epley maneuver with medical therapy provides effective and longterm control of symptoms in patients with BPPV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Munjal et al 84.81% of the patients got symptomatic relief with Epley maneuver. 2 Through a series of head movements, the crystals are returned to the utricle, where they are either absorbed or eliminated by the endolymphatic sac. 21 However a study done by Kavathia et al showed that the Epley maneuver with medical therapy provides effective and longterm control of symptoms in patients with BPPV.…”
Section: Discussionmentioning
confidence: 99%
“…Possible etiology includes idiopathic, inflammatory insult (Viral) and trauma. 2 A study by Arya and Nunezhad showed 22% patients to be of BPPV. 3,4 A study by Bansal et al had 18.75% patients as BPPV.…”
Section: Introductionmentioning
confidence: 99%